Attitudes of typically developing students toward inclusive education in the Republic of Srpska - Bakoč, Andrijana (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Attitudes of typically developing students, their preparation for acceptance, and cooperation with peers with disabilities are important factors for the realization and success of inclusive education. Objective. The aim of the research was to determine the attitudes of typically developing students toward inclusive education and their relation to the attitudes toward people with disabilities, frequency of contact, classroom climate, gender, and class. Methods. The sample included 331 students from 3rd to 5th grade of regular primary school. The sample was divided into two subsamples: participants attending inclusive and non-inclusive classes. The following scales were used for evaluation: Peer Attitude Toward the Handicapped Scale, Chedoke‒McMaster Attitudes Towards Children with Handicaps Scale, The Contact with Disabled Persons Scale, and My Class Inventory. Results. The results show that students’ attitudes toward inclusive education of peers with disabilities are mostly negative. The most important predictors of their attitudes were: frequency of contact, disagreements, competitiveness, and grade. On the other hand, attending classes with peers with disabilities, attitudes toward them, satisfaction with the class, and gender were not the predictors of importance. Conclusion. The results indicate the need for early preparation of students with typical development for joint education with peers with disabilities through contact and nurturing a collaborative climate in the classroom.